PENGARUH PENGAWASAN KERJA DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA DENGAN TEAMWORK SEBAGAI MODERASI PADA PEGAWAI BAGIAN PENYULUH LAPANGAN DINAS PETERNAKAN DAN PERKEBUNAN KABUPATEN ROKAN HULU - Rizana, Yopi; Seprini, Seprini; Hidayat, Hidayat (Komunitas Manajemen Kompetitif, 2025)
This study aims to determine the effect of supervision and work experience on productivity, with teamwork as a moderator. The study population was field extension workers at the Animal Husbandry and Plantation Service of Rokan Hulu Regency. A sample size of 53 respondents was determined using saturated sampling. The independent variables in this study were supervision and work experience, teamwork as a moderator, and productivity as a dependent variable. Data analysis techniques used were Structural Equating Modeling (SEM PLS) and Smart PLS. The results showed that supervision had a positive but insignificant effect on productivity, work experience had a significant positive effect on productivity, and supervision had a positive but insignificant effect on teamwork. Work experience had a positive and significant effect on teamwork. Teamwork had a significant positive effect on productivity.